Помогите решить Упростите выражение: а) (а - 2) + (а - 3) - (2а + 7)= б) 2 * (а - 3) - (5а + 6)= в) -3 * (2х - 9) + (-5х + 1)= г) (х - 3) + (х - 5) - (7 - 3х)= д) -2 * (m - 3) - (3m - 5)= е) 4 * (2а - 1) + (7 - 5а)=

Помогите решить Упростите выражение: а) (а - 2) + (а - 3) - (2а + 7)= б) 2 * (а - 3) - (5а + 6)= в) -3 * (2х - 9) + (-5х + 1)= г) (х - 3) + (х - 5) - (7 - 3х)= д) -2 * (m - 3) - (3m - 5)= е) 4 * (2а - 1) + (7 - 5а)=
Гость
Ответ(ы) на вопрос:
Гость
а) (а - 2) + (а - 3) - (2а + 7)=a-2+a-3-2a-7=-12 б) 2 * (а - 3) - (5а + 6)=2a-6-5a-6=-3a-12 в) -3 * (2х - 9) + (-5х + 1)=-6x+27-5x+1=-11x+28 г) (х - 3) + (х - 5) - (7 - 3х)=x-3+x-5-7+3x=5x-15 д) -2 * (m - 3) - (3m - 5)=-2m+6-3m+5=-5m+11 е) 4 * (2а - 1) + (7 - 5а)= 8a-4+7-5a=3a+3
Не нашли ответ?
Ответить на вопрос
Похожие вопросы